USO de aditivos para consevarção de pêssegos 'Aurora-1' minimamente processados - Martins, Ramilo Nogueira [UNESP]; Mattiuz, Ben-Hur [UNESP]; Santos, Leandra Oliveira [UNESP]; Morgado, Cristiane Maria Ascari [UNESP]; Mattiuz, Claudia Fabrino Machado [UNESP] (FapUNIFESP (SciELO), 2011)
'Aurora-1' peaches establishes an interesting alternative as a minimally processed product, due to its characteristics like flavor, color, smell, and also because of its handling resistance. However, it has a short shelf life after a fresh-cut due to enzymatic browning and stone cavity collapse. The main purpose of this research was to test the additive with antioxidant effect to prevent browning in minimally processed 'Aurora-1' peaches. The minimal processing consists of washing, sanitizing, peelings and fruit stone extraction. After that, longitudinal cuts were made to obtain eight segments per fruit. The slices were immersed into the following treatment solutions: control (immersion in 2% ascorbic acid); 2% ascorbic acid + 2% calcium chloride; 1% sodium isoascorbate; 1% citric acid; 1% L-cysteine hydrochloride. The products were placed into rigid polystyrene trays branded MEIWA M-54, covered with 14 μm PVC film (Omnifilm™) and kept in cold storage at 3°C ± 2°C and 65% RH for twelve days, and evaluated each three days. Appraised variables were appearance, soluble solids, titratable acidity, soluble carbohydrates and reducing sugars, total and soluble pectin, ascorbic acid, and peroxidase and polyphenol oxidase enzyme activity. L-cysteine gave to the minimally processed products a shelf life of twelve days, limmited by off-flavor. The treatment with ascorbic acid was efficient to maintainthe ascorbic acid content, with a shelf-life of nine days, limited by enzymatic browning.
Preservation of minimally processed 'Aurora-1' peaches using additives
Keywords: Ascorbic acid; Calcium chloride; Citric acid; Cysteine; Isoascorbate